Effect of Liquidity and Capital Structure on Profitability in Manufacturing Company Listed In Indonesia Stock Exchange Period 2015-2016 - Suhendro, Piggy Aprilia Pangastuti, Endang Masitoh & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to determine whether there is a partial influence Current Ratio,Quick Ratio, Debt to Equity Ratio and Total Assets Turnover on Profitability(Return On Assets). This research uses quantitative data. The population used inthis study is a manufacturing company listed on the Indonesia Stock Exchangeperiod 2015-2016. The method used in this study is purposive sampling andobtained a sample of 71 companies for each year in the period 2015-2016, so thatobtained as many as 142 data observation. Data analysis method used is multiplelinear regression analysis. The result of research partially states that the variableof Total Assets Turnover influence to Profitability (Return On Assets), whilevariable of Current Ratio, Quick Ratio and Debt to Equity Ratio have no effect toProfitability (Return On Assets). Based on regression analysis, we found that CR ,QR, DER and TATO have a significant effect on Profitability (ROA).Keywords: Liquidity, Solvency, Activity and Profitability